Investigating the Relationship Between Internet Addiction and Academic Archievement of Medical Students (2013) - Rita Motidost Komleh; Agha Fatemeh Hosseini; Ladan Fata; Fakhrossadat Mirhosseini; Shoaleh Bigdeli (Iranian Journal of Health, Safety and Environment, 2016)
Intensive use of the internet can be associated with negative psychological consequences and behavioral changes. These consequences affect different aspects of life including physical, mental and spiritual health and academic performance of the students as users. In this regard, this study is an attempt to determine the rate of internet addiction and its relationship to academic achievement among medical students of basic sciences studying at Tehran University of Medical Sciences. In this cross-sectional study, a sample size of 417 participants had been selected by stratified random sampling. To collect data a demographic questionnaire and a Farsi version of Young Internet Addiction Test was used. Descriptive statistics (frequency distribution, frequency Percent, mean and standard deviation) and inferential statistics (Pearson correlation test, chi-square and t-test) were used to analyze data. 57 out of 417 participants of the study (15.2%) had internet addiction. There was a significant relationship between time spent on the internet (p≤0.001) and number of failed credits in the semester prior to the study (P≤0.02 and r=-0.136). Internet addiction was not significantly associated with sex, age, age of the first internet use, parental education and academic achievement. By medical students of basic sciences internet addiction had no significant relationship with academic achievement; however, to study the effects of Internet addiction on other aspects of medical students' life is suggested.